Membangun Keterampilan Desain Komunikasi Visual melalui Workshop Kolaboratif antara Guru dan Siswa di Kota Metro - Kurniawan, Dwi; Solihin (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
This study aims to explore the impact of a visual communication design workshop involving collaboration between teachers and students in Metro City, focusing on enhancing students' technical skills, creativity, and collaborative abilities. The workshop, organized by the Metro Arts Council, involved 10 junior high school teachers, 10 senior high school students, and 10 junior high school students. This research uses a qualitative approach with a case study method, where data were collected through observations, interviews, and questionnaires distributed to the workshop participants. The main findings of this study indicate that the collaborative workshop effectively improved students' technical skills in using graphic design software and deepened their understanding of design principles. 85% of students reported feeling more proficient in using design tools, and 78% reported an increase in creativity after attending the workshop. Additionally, 90% of students felt an improvement in their collaborative skills when working in teams. This study also shows that a collaborative learning approach not only enriches students' technical skills but also stimulates their creativity and innovation, as well as enhances their ability to work in groups. Based on these findings, it is recommended to integrate visual communication design workshops into school curricula and provide training for teachers to support more effective collaborative learning.